Life after party ; the high cost of dying ; Horror SFX - Gancia, Carol; Lazaro, Cheche; Nakpil, Henry; Ong, James Jonathan (The Probe Team, 1995)
Presents viewpoints of Christians, Hindus, Ignostics, skeptics, after-life believers on life after death ; funeral parlor servicing bereaved families of all social classes ; and the use of computer softwares and high tech mainframes in creating unearthly things like ghost and in transforming a normal person to monster.